Hidden targets in dermatology: In vitro and In silico inhibitory effects of common 23 dermatologic drugs on human carbonic anhydrase isoenzymes I and II - Can, Ilkay; Cikrikci, Kubra; Gencer, Nahit; Uslu, Harun (Taylor & Francis Ltd, 2025)
In this study, we have aimed to determine the in vitro and in silico effects of 23 frequently used dermatologic drugs on human carbonic anhydrase I (hCA I) and II (hCA II). The inhibitory effects of the drugs on hCA I and hCA II were determined by esterase methods. The most potent inhibitors were isotretinoin for hCA I (Ki= 5.75 mu M) and valaciclovir for hCA II (Ki= 5.74 mu M). Ketotifen (Ki= 6.98 mu M), pantoprazole (Ki= 7.16 mu M) and acyclovir (Ki= 7.31 mu M) were also potent inhibitors for hCA I. Isotretinoin (Ki= 6.54 mu M), brivudine (Ki= 7.44 mu M) and fluconazole (Ki= 7.91 mu M) were also potent inhibitors for hCA II. Terbinafine hydrochloride was a weak CA inhibitor for both of these isoenzymes (Ki= 20.58 mu M for hCA I and 20.32 mu M for hCA I). Therefore, the drug, having a weak CA inhibitory activity, may be preferred primarily in patients with a skin disease compared to the other drugs due to important physiological functions of CAs. Molecular docking studies have shown that acitretin and isotretinoin, in particular, will inhibit hCA I at lower concentrations and have higher docking scores. For hCA II, it was shown that Isotretinoin and Ketotifen would inhibit at lower concentrations and have higher placement scores.
Keywords: Carbonic anhydrase; dermatologic drugs; enzyme inhibition; molecular docking